2004
DOI: 10.1177/1368430204039975
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Reactions to Sexist Humor

Abstract: This research investigated the relation between sexism, general prejudice, and reactions to sexist humor. Eighty-one male participants completed measures of modern sexism, ambivalent sexism, right-wing authoritarianism, and social dominance orientation, and rated the funniness, offensiveness, and likelihood of repeating female-disparaging and male-disparaging jokes. Results revealed that men who were higher in hostile sexism were especially likely to report that they would repeat the female-disparaging jokes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 19 publications
7
77
1
1
Order By: Relevance
“…Eyssel and Bohner 2007;Hunt and Gonsalkorale 2014). Several studies demonstrate that individuals high in hostile sexism enjoy sexist humour significantly more than individuals low in hostile sexism (Greenwood and Isbell 2002;LaFrance andWoodzicka 1998, Thomae andViki 2013) and are more willing to repeat female-disparaging jokes to friends (Thomas and Esses 2004). These findings comfortably fit with Ford and Ferguson's (2004) and Woodzicka and Ford's (2010) conceptualisation of sexist humour as a 'releaser' of prejudice.…”
Section: Responses To Sexist Humour As a Function Of Gender Attitudessupporting
confidence: 76%
See 1 more Smart Citation
“…Eyssel and Bohner 2007;Hunt and Gonsalkorale 2014). Several studies demonstrate that individuals high in hostile sexism enjoy sexist humour significantly more than individuals low in hostile sexism (Greenwood and Isbell 2002;LaFrance andWoodzicka 1998, Thomae andViki 2013) and are more willing to repeat female-disparaging jokes to friends (Thomas and Esses 2004). These findings comfortably fit with Ford and Ferguson's (2004) and Woodzicka and Ford's (2010) conceptualisation of sexist humour as a 'releaser' of prejudice.…”
Section: Responses To Sexist Humour As a Function Of Gender Attitudessupporting
confidence: 76%
“…Similarly, Thomas and Esses (2004) demonstrated that hostile sexism positively correlated with the perceived funniness and negatively correlated with the perceived offensiveness of sexist jokes, as well as men's likelihood to repeat female disparaging jokes. Irrespective of their own sex, participants who held pro-feminist attitudes showed lower appreciation for sexist cartoons, independently of whether the target of the disparagement was male or female (Henkin and Fish 1986).…”
Section: Using a Staged Recorded Conversation Between Two Male Confedmentioning
confidence: 99%
“…As expected RWA did not predict reactions to disparaging outgroup (or neutral) jokes (see Thomas & Esses, 2004). UO was negatively related with Mexican joke reactions, as predicted.…”
Section: Relations Between Chb and Intergroup-relevant Variablessupporting
confidence: 67%
“…Greenwood and Isbell (2002) found that men and women high in hostile sexism-that is, antagonism toward women (Glick and Fiske 1996)-were more amused by and less offended by Bdumb blonde^jokes than were men and women low in hostile sexism. In similar fashion, Thomas and Esses (2004) found that men reported more enjoyment of femaledisparaging jokes and a greater likelihood of telling those jokes insofar as they were high in hostile sexism.…”
Section: Sexist Humor As An Expression Of Sexismmentioning
confidence: 58%